Reliability of sternal instability scale (SIS) for transverse sternotomy in lung transplantation (LTX). (2nd December 2018) - Fuller, Louise M; El-Ansary, Doa; Button, Brenda; Bondarenko, Janet; Marasco, Silvana; Snell, Greg; Holland, Anne E
ABSTRACT: A surgical incision for bilateral sequential lung transplantation (BSLTX) is the "clam shell" (CSI) approach via bilateral anterior thoracotomies and a transverse sternotomy to allow for sequential replacement of the lungs. This can be associated with significant post-operative pain, bony overriding or sternal instability. The sternal instability scale (SIS) is a non-invasive manual assessment tool that can be used to detect early bony non-union or instability following CSI; however, its reliability is unknown. Objective : This prospective blinded reliability study aimed to assess intra-rater and inter-rater reliability of the SIS following lung transplantation. Method : Participants post BSLTX aged older than 18 years underwent sternal assessment utilizing the SIS. Two assessors examined the sternum using a standardized protocol at two separate time points with a test–re-test time of 48 hours. The outcome measure was SIS tool using four categories from 0 (clinically stable) to 3 (separated sternum with overriding). Results : In total, 20 participants (75% female) with a mean age of 48 years (SD 17) and mean pain score of 3 out of 10 were included, 60% having well healed wounds and 25% reporting symptoms of sternal clicking. The most painful self-reported painful activity was coughing. The SIS demonstrated excellent reliability with a kappa = 0.91 by different assessors on the same day, and kappa = 0.83 for assessments by the same assessor on different days. Conclusion : The SIS is a reliable manual assessment tool for evaluation of sternal instability after CSI following BSLTX and may facilitate the timely detection and management of sternal instability.